Within-Person Associations Between Attachment Security, Need Satisfaction and Psychological Adjustment in Daily Life of Older Adults. (10th November 2019) - Martin, Annika A; Horn, Andrea B; Allemand, Mathias
Abstract: Objectives: Little is known about how attachment processes manifest within older adults in daily life and how these processes are associated with daily psychological adjustment. This study examined the within-person associations between states of attachment security and psychological adjustment. It is expected that this association is mediated by higher levels of satisfied needs in daily life. Methods: Microlongitudinal self-report data were collected in a sample of 136 older adults ranged in age from 60 to 90 years (age M = 70.45 years) across 10 days with daily morning and afternoon measurement occasions. Results: Three main findings from multilevel analyses emerged. First, older adults showed significant within-person variation in attachment security, satisfaction of the needs for autonomy and competence, and psychological adjustment over time. Second, attachment security was positively associated with psychological adjustment within individuals. Third, both satisfaction of the needs for autonomy and competence mediated the within-person association between attachment security and psychological adjustment. Discussion: The results suggest that attachment security is associated with the experience of autonomy and competence in daily life of older adults which in turn is related with better psychological adjustment.